22.9k views
1 vote
Use the denition of the derivative to find f 0 (3), where f (x) = 3x+5 / 2x−1

User Visc
by
5.5k points

1 Answer

2 votes

Answer:


f'(3)= -(13)/(25)

Explanation:

We are asked to find
f'(3) of function
f(x)=(3x+5)/(2x-1) using definition of derivatives.

Limit definition of derivatives:


f'(x)= \lim_(h \to 0) (f(x+h)-f(x))/(h)

Let us find
f(3+h) and
f(3).


f(3+h)=(3(3+h)+5)/(2(3+h)-1)


f(3+h)=(9+3h+5)/(6+2h-1)\\\\f(3+h)=(3h+14)/(2h+5)


f(3)=(3(3)+5)/(2(3)-1)


f(3)=(9+5)/(6-1)\\\\f(3)=(14)/(5)

Substituting these values in limit definition of derivatives, we will get:


f'(3)= \lim_(h \to 0) (f(3+h)-f(3))/(h)


f'(3)= \lim_(h \to 0) ((3h+14)/(2h+5)-(14)/(5))/(h)

Make a common denominator:


f'(3)= \lim_(h \to 0) (((3h+14)*5)/((2h+5)*5)-(14(2h+5))/(5(2h+5)))/(h)


f'(3)= \lim_(h \to 0) ((5(3h+14)-14(2h+5))/(5(2h+5)))/(h)


f'(3)= \lim_(h \to 0) (5(3h+14)-14(2h+5))/(5h(2h+5))


f'(3)= \lim_(h \to 0) (15h+70-28h-70)/(5h(2h+5))


f'(3)= \lim_(h \to 0) (-13h)/(5h(2h+5))

Cancel out h:


f'(3)= \lim_(h \to 0) (-13)/(5(2h+5))


f'(3)= (-13)/(5(2(0)+5))


f'(3)= (-13)/(5(5))


f'(3)= -(13)/(25)

Therefore,
f'(3)= -(13)/(25).

User Unix One
by
5.2k points